Implementing a demand side management strategy for harmonics mitigation in a smart home using real measurements of household appliances - Cicek, Alper; Erenoglu, Ayse Kubra; Erdinc, Ozan; Bozkurt, Altug; Tascikaraoglu, Akin; Catalao, Joao P. S. (ELSEVIER SCI LTD, 2021)
Significant developments on semiconductor technology have captured the electronic industry and paved the way for dominating household appliances market. Typical loads in this market generally have nonlinear voltage current characteristics. Therefore, highly-integrated power-electronic based electrical equipment in the demand side has caused harmonic pollution, which is one of the most important power quality problems in distribution system operation. To address this issue, there have been significantly great attempts to keep total harmonic distortion (THD) and total demand distortion (TDD) levels within International standard limits defined by IEEE 519 and IEC 61000. On the other hand, load shifting has recently drawn special attention of power grid planners to improve system performance substantially in the smart grid paradigm. In this study, the real harmonic measurements of residential appliances (both linear and nonlinear) are carried out in the Smart Home Laboratory in Yildiz Technical University, Istanbul, Turkey. Different load profiles are then created with a high accuracy based on the measured voltage and current, active, reactive and apparent power. Also, three case studies are considered to investigate the impacts of load shifting strategies on power quality requirements in terms of satisfying the relevant standards. As a result, it is shown that the TDD value decreases below nearly 8% limitation by mitigating the harmonic distortion and the TDD index, which indicates the harmonic distortion effect on the system regarding the desired standard limits of IEEE.
Keywords: Harmonic current; Harmonic distortion; Load shifting; Smart home; Total demand distortion; Engineering